2007
DOI: 10.1038/sj.jid.5700661
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of μ- and κ-Opioid Receptors in Mice Changes Epidermal Hypertrophy, Density of Peripheral Nerve Endings, and Itch Behavior

Abstract: The mu- (MOR) and kappa- (KOR) opioid receptors have been implicated in the regulation of homeostasis of non-neuronal cells, such as keratinocytes, and sensations like pain and chronic pruritus. Therefore, we have studied the phenotype of skin after deletion of MOR and KOR. In addition, we applied a dry skin model in these knockout mice and compared the different mice before and after induction of the dermatitis in terms of epidermal thickness, epidermal peripheral nerve ending distribution, dermal inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 51 publications
(63 reference statements)
0
55
0
2
Order By: Relevance
“…The epidermis of MOR knockout mice is thinner than that of wild-type mice. 41 Selective loss of motor and sensory nerve after neuronal injury also results in epidermal thinning. 42 Therefore, down-regulation of MOR and reduction in innervation of the skin of mice expressing HbS, as observed by us, may contribute to thinning of the epidermis.…”
Section: Structural and Neurochemical Changes In Mice Expressing Hbsmentioning
confidence: 99%
“…The epidermis of MOR knockout mice is thinner than that of wild-type mice. 41 Selective loss of motor and sensory nerve after neuronal injury also results in epidermal thinning. 42 Therefore, down-regulation of MOR and reduction in innervation of the skin of mice expressing HbS, as observed by us, may contribute to thinning of the epidermis.…”
Section: Structural and Neurochemical Changes In Mice Expressing Hbsmentioning
confidence: 99%
“…The expression of m-opioid and k-opioid receptors was detected at reduced levels in skin biopsies of atopic dermatitis patients due to its internalization in keratinocytes [69]. Interestingly, dry skin induction in mice with deleted cutaneous m-opioid receptor revealed that these mice scratch less often than their wild type counterparts, indicating an important role in itch sensation and skin homeostasis [70].…”
Section: Neuroimmune Interactions In Skin Pathophysiologymentioning
confidence: 97%
“…Enkephalins such as [Met 5 ] and [Leu 5 ]-enkephalin and the synthetic d-Ala-d-Leu-enkephalin have been reported to inhibit cell differentiation dose-dependently in human keratinocytes in vitro, while β-endorphin had no effect [38]. Deletion of the classical opioid receptors in mice resulted in a phenotype of thinner epidermis and higher expression of differentiation markers, whereas a burn wound healed significantly slower in these KO mice relative to wildtype mice [31,32]. Naloxone and naltrexone (NTX) are general opioid antagonists that are devoid of intrinsic biological actions [39] and block the interaction of three opioid peptide families (prodynorphin, proopiomelanocortin, proenkephalin) and classical (μ, δ, κ) as well as non-classical (OGFr) opioid receptors.…”
Section: Opioids Opioid Receptors Opioid Antagonists and Skinmentioning
confidence: 99%
“…Several endogenous opioids (enkephalins, endorphins, dynorphins, endomorphins) and classical (μ/MOR/Oprm1, δ/DOR/Oprd1, κ/KOR/Oprk1) opioid receptors, as well as the nuclear-associated, non-classical OGFr are present and functioning in skin [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Enkephalins such as [Met 5 ] and [Leu 5 ]-enkephalin and the synthetic d-Ala-d-Leu-enkephalin have been reported to inhibit cell differentiation dose-dependently in human keratinocytes in vitro, while β-endorphin had no effect [38].…”
Section: Opioids Opioid Receptors Opioid Antagonists and Skinmentioning
confidence: 99%
See 1 more Smart Citation